IF WE KNEW THEN WHAT WE KNOW NOW: THE PREPAREDNESS EXPERIENCE PRELOSS AND POSTLOSS FOR DEMENTIA CAREGIVERS. (11th November 2018) - Supiano, K; Luptak, M K; Christian Andersen, T; Beynon, C
Abstract: Meaning-making - the capability of grievers to accept loss, realize growth, and reorganize personal identity – contributes to healthy grief. We evaluated grief preparedness and grief experience in 50 family caregivers (FCGs) anticipating death of their care recipient (CR) within 6 months, and 50 FCGs who experienced the death of their CR in the prior 6 months. Using a phenomenological lens to discern meaning-making in narratives, we found that when preparation included positive memory construction, perception of death as ending CR suffering, relationship resolution, dementia understanding, and shared construction of meaning with family, it predicted positive grief. Inadequate preparation included trauma as CR declined, loss of caregiver role, perceived unavailability of support, loneliness and difficulties creating a life without CR. Inadequate preparation was associated with difficulty making meaning of the illness, death and poorer grief. These findings inform understanding of meaning-making as a mediating process in preparation and healthy grief.